Educator Vincas Ruzgas - Bernotas, Vytautas (Acta Paedagogica Vilnensia, 1997)
The article presents pedagogical legacy of a prominent cultural and educational figure – Vincas Ruzgas (1890-1972), and analyses the dissemination of his pedagogical ideas and their relevance in today’s schools. Ruzgas had written over 650 publications, and had published 31 books, focusing on didactics, child and adult education, history of pedagogy, ethnographic problems. But the main areas of interest for Ruzgas was the science teaching and methodology of learning. In his methodological aids for teachers and students, articles, and textbooks he was providing very detailed methodological guidelines for teaching and learning natural science, and examples for their practical realization. Ruzgas emphasized the independent research work, stressed value-related aspects of natural science and environmental issues.